2022
DOI: 10.1002/eap.2720
|View full text |Cite
|
Sign up to set email alerts
|

Landscape‐level heterogeneity of agri‐environment measures improves habitat suitability for farmland birds

Abstract: Agri‐environment schemes (AESs), ecological focus areas (EFAs), and organic farming are the main tools of the common agricultural policy (CAP) to counteract the dramatic decline of farmland biodiversity in Europe. However, their effectiveness is repeatedly doubted because it seems to vary when measured at the field‐versus‐landscape level and to depend on the regional environmental and land‐use context. Understanding the heterogeneity of their effectiveness is thus crucial to developing management recommendatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 52 publications
0
5
0
Order By: Relevance
“…As we focused on grassland-based AES, we excluded grid cells with less than 1 ha of permanent grassland, which is the approximate territory size of the species (Brambilla et al 2009). The Catalan dataset (Roilo 2023) was additionally filtered to remove grid cells at elevations below 200 m a.s.l. and above 2000 m a.s.l., which are outside the altitudinal range limits of the red-backed shrike in Catalonia (Rodríguez-Franch et al, 2021).…”
Section: Environmental Datamentioning
confidence: 99%
See 1 more Smart Citation
“…As we focused on grassland-based AES, we excluded grid cells with less than 1 ha of permanent grassland, which is the approximate territory size of the species (Brambilla et al 2009). The Catalan dataset (Roilo 2023) was additionally filtered to remove grid cells at elevations below 200 m a.s.l. and above 2000 m a.s.l., which are outside the altitudinal range limits of the red-backed shrike in Catalonia (Rodríguez-Franch et al, 2021).…”
Section: Environmental Datamentioning
confidence: 99%
“…We collated environmental variables known to influence the red-backed shrike distribution (Brambilla et al 2009, Roilo et al 2023. For each 1 km grid cell, we extracted the mean elevation (m; ELEVATION) from the Copernicus EU-DEM v1.1 and the maximum temperature ( • C, TMAX) and the sum of mean monthly precipitation (mm, PRECIP) between May and July, corresponding to the red-backed shrike breeding period, from the CHELSA Climatologies 1981-2010 V2.1 (Karger et al 2017(Karger et al , 2020.…”
Section: Environmental Datamentioning
confidence: 99%
“…Therefore, they implicitly assume the existence of a common ecological scale for all predictor variables. However, it has been shown that the ecological scale is variable-specific since species often respond to different environmental variables at different spatial scales and sometimes even respond differently to a single environmental variable at multiple grains (Leitão et al, 2010; Lecours et al, 2020; Miguet et al, 2016; Roilo et al, 2022). However, despite theoretical concepts and extensive empirical evidence that species respond to their environment at different spatial grains (e.g.…”
Section: Single-grain Versus Multi-grain Analysismentioning
confidence: 99%
“…For example, the limited effectiveness of agri-environment schemes (Batary et al 2015) can be attributed to the pronounced variability and nonlinearity in relationships between agriculture and farmland biodiversity, e.g. in protecting farmland birds (Whittingham et al 2007, Concepcion et al 2020, Roilo et al 2023. Therefore, land-use policies that are tailored to fit the characteristics of specific land systems are more effective than homogeneously implemented measures (Young 2013, Nolte et al 2017).…”
Section: Introductionmentioning
confidence: 99%